Pembangunan Daerah dan Pengembangan Kecamatan (Dalam Prespektif Teori dan Implementasi) - Sumodiningrat, Gunawan (Journal of Regional and City Planning, 1999)
The objective of development is to improve the standard, status, quality, and welfare of the society; therefore, development should be perceived as a series of continuous changes to achieve that objective. The effectiveness of development at the local level is very strategic since it determines the effectiveness of regional development to achieve the objective of national development. The strengthening of development institution at the local level in an effort to achieve regional autonomy and also an effort to improve the interconnection among various levels in planning mechanism and the implementation of development programs. The strengthening of  local institution is a way to implement the three directions of regional development: society empowerment, solidify regional autonomy, and modernization through natural structural changes